Les libéraux de gauche allemands et la France avant 1914 - Philippe Alexandre (Recherches Germaniques)
In the years leading up to the First World War, peace initiatives were developed by German politicians in the midst of growing tensions in Europe. These politicians included left-wing liberals, i.e. members of the splinter parties that came together in 1910 to form the Fortschrittlichen Volkspartei. They demanded more democracy and more social justice, in run-off elections and in parliaments they were able to join forces with the Social Democrats; however, a number of them were also characterized by their commitment to peace. For them, it was not a question of preaching peace at any costs, but of giving long lasting peace a chance. The peace work they carried out alongside or in cooperation with the Social Democrats concentrated mainly on three areas in which they hoped to influence public opinion in line with their ideas, namely the press, schools and inter-parliamentary organizations. However, the counteraction of their opponents and the outbreak of war in August 1914 proved how futile their efforts were.